Govorice dvojezičnih literarnih oseb iz osrednjeslovenskega in beneškoslovenskega prostora - Curk, Mateja (Jezik in slovstvo, 2016)
The paper deals with contemporary literary texts written by authors living in the province of Udine (Italy) and belonging to the community of so-called Venetian Slovenians (Besiede tele zemlje 2004), as well as a literary work from the central part of Slovenia (Čefurji raus! 2008). Taking into account the tendency of these texts to reflect real-language use, ideological aspects of literary discourse based on language varieties from different parts of the Slovene-speaking territory are discussed.
Keywords: Vojnović, Goran, 1980-; "Čefurji, raus!"; Slovene; slovenščina; Vojnović, Goran: Čefurji raus!; bilingualism; dvojezičnost; jezikovna ideologija; literarni jezik; Slavia Friulana; Beneška Slovenija; Slovenia; Slovenija